THE CHARACTERISTICS OF THE IMPAIRED FUNCTIONS AND LIFE LIMITATIONS OF THE DISABLED PEOPLE DUE TO THE CORONARY HEART DISEASE - N.N. Shmakova; S.N. Puzin; N.S. Zarariy; А.V. Abol (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
The article presents the characteristics of the impaired functions and life limitations of the disabled people due to the coronary heart disease with consideration to clinical data, the disease stages and the disability severity. It was revealed that the largest share in the structure of impaired functions was made up by the impaired functions of the cardiovascular neuromuscular, movement-related (statodynamic), endocrine systems and metabolism and life limitations of I, II and III degrees related to self-care, movement and labour activity.